A Shared Vision on the 2004 Indian Ocean Tsunami in Malaysia: Hazard Assessments, Post-Disaster Measures and Research - Moon W.C.; Sidek L.M.; Lau T.L.; Puay H.T.; Majid T.A.; Wahab A.K.A.; Teo F.Y. (MDPI, 2023)
The tsunami is one of the deadliest natural disasters, responsible for more than 260,000 deaths and billions in economic losses over the last two decades. The footage of the devastating power of the 2004 Indian Ocean tsunami perhaps remains vivid in the memory of most survivors, and Malaysia was one of the countries affected by the unprecedented 2004 tsunami. It was the first time the Malaysian government had managed such a great disaster. This review, therefore, gathers the relevant literature pertaining to the efforts undertaken following the event of the 2004 tsunami from Malaysias perspective. A compilation of post-event observations regarding tsunami characteristics is first presented in the form of maps, followed by building damage, including damage modes of wall failure, total collapse, debris impact and tilting of structures. In addition, hazard assessments and projections regarding a hypothetical future tsunami towards vulnerable hazard zones in Malaysia are reviewed. It is observed that future tsunami risks may originate from the Indian/Burma Plate, Andaman Island, Sunda Trench, Manila Trench, Sulu Trench, Negro Trench, Sulawesi Trench, Cotabato Trench and Brunei slide. A rundown of post-2004 measures and tsunami research undertaken in the country is also included in this review, serving as a reference for disaster management globally. Overall, the outcomes of this review are important for understanding tsunami vulnerability and the resilience of coastal infrastructures, which will be crucial for continued progress in the future. 2022 by the authors.